Pencegahan Stunting Melalui Pendidikan Pada 1000 Hari Pertama Kehidupan di Desa Lima Poccoe, Kabupaten Maros - Jayadi, Yusma Indah; Sari, Novita; Alfina, Afiah; Wijaya, Dian Rezki; Adnan, Yudi (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
As Based on WHO limits, Indonesia is in the category of high stunting problems. So that fulfilment of nutritional intake at 1000 Day First, the child's life is very important. If in that age range the child gets optimal nutritional intake, the decline in the child's nutritional status can be prevented from the start. This research uses quantitative research with purposive sampling technique. This study uses quasi-experimental designs with a one-group pretest-posttest.The research population is all WUS, IRT, and pregnant women who live in Samata and Kampala Hamlets, Limapoccoe Village, totaling 242 residents who are female. Respondents in this study amounted to 30 respondents. The variables seen in this study are Knowledge and Attitudes Regarding the First 1000 Days of Life. This research was conducted in December 2021. Data processing was carried out in a descriptive-analytic manner with the Wilcoxon test. The results of the research conducted on the level of community knowledge in the Samata hamlet regarding the importance of the First 1000 Days of Life there was a significant difference (p-value 0.00) in the knowledge of the community before and after the counseling was carried out, while the attitude of the community when participating in the counseling the results obtained by the residents of the Samata hamlet did not have a difference. before and after the activity (p-value 1.00). It is necessary to have an integrated counseling program carried out by the puskesmas or posyandu cadres so that there is an increase in knowledge and attitudes of 1000 DoL which can prevent stunting in generations.